1988
DOI: 10.1002/ana.410230208
|View full text |Cite
|
Sign up to set email alerts
|

Increases in both cerebral glucose utilization and blood flow during execution of a somatosensory task

Abstract: To investigate local metabolic and hemodynamic interrelationships during functional activation of the brain, paired studies of local cerebral glucose utilization (lCMRGlc) and blood flow (lCBF) were carried out in 10 normal subjects (9 right-handed, 1 ambidextrous) at rest and during a unilateral discriminative somatosensory/motor task--palpation and sorting of mah-jongg tiles by engraved design. The extent of activation was assessed on the basis of percentage difference images following normalization to compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Therefore, the caveat remains that the reported differences between right and left hemisphere activation were related to factors other than hemispheric dominance. Ginsberg et al (1988), using a complex somatosensory discriminative task, observed differences in CMR glu induced by the movements of the right and the left hands. It remains difficult to use 18F-fluorodeoxyglucose for activation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the caveat remains that the reported differences between right and left hemisphere activation were related to factors other than hemispheric dominance. Ginsberg et al (1988), using a complex somatosensory discriminative task, observed differences in CMR glu induced by the movements of the right and the left hands. It remains difficult to use 18F-fluorodeoxyglucose for activation studies.…”
Section: Discussionmentioning
confidence: 99%
“…With this technique, we observed a 16.9% increase in local cerebral glucose utilization and a 26.6% increase in local cerebral blood flow in normals. 14 The video game that we employed is obviously a crude task that would be expected to activate a number of different areas of the cerebral cortex as it requires attention, visual input, visuospatial orientation, and fine motor activity. Its most attractive feature was that successful manipulation of the joystick, resulting in progressive removal of bricks from the wall, routinely resulted in prolonged attention.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation-induced changes in CMRO 2 , CMR glc , and CBF in the awake human brain from PET studies are shown. [12][13][14][15][16][17][18][19][20][21][22][23] Inset shows distribution of ⌬CMRO 2 /CMRO 2 , ⌬CMR glc /CMR glc , and ⌬CBF/CBF values from the PET studies (Table); exact values and their implications are discussed elsewhere. 24,25 The difference between changes in CMR glc and CMRO 2 (ie, ⌬CMR glc /CMR glc Ϫ⌬CMRO 2 /CMRO 2 on the vertical axis) reflects the degree of glucose oxidation; the lower the difference is, the greater is the degree of glucose oxidation (Equation 1).…”
Section: Physiology Of Neuroimagingmentioning
confidence: 99%